Implementation of Dual Axis Solar Tracking System. Issue 1 (March 2021) - Mohanapriya, V; Manimegalai, V; Praveenkumar, V; Sakthivel, P
Abstract: As a future inexhaustible and non-polluting energy sources, solar energy is advancing to meet our ever-growing energy requirements. The automated solar tracking system based on the Arduino prototype is mainly built using the Arduino Microcontroller, four LDRs and three stepper motors. A mixture of hardware and firmware programming is used to run the machine. Four light based resistors (LDRs) are used for the capture of maximum incident light in hardware production. To shift the solar panel according to the extent incident light operated by LDRs, three stepper motors are used. The software controls the solar panel's vertical tilt angle and horizontal rotation. Thus, according to the incident sunlight on the solar panel, it can follow the direction of the Sun, not only the vertical rotation, but also the horizontal rotation. This device can also achieve optimum illumination and reduce the cost of generating energy by requiring a minimum number of solar panels.